Following the father steps in the bowels of the Earth: The ichnological record from the Bàsura Cave (Upper Palaeolithic, Italy) - Avanzini, Marco (2021)
The chapter summarizes the new results of the Bàsura Revisited Interdisciplinary Research Project. The integrated interpretation of recent archaeological data and palaeosurface laser scans, along with geoarchaeological, sedimentological, geochemical and archaeobotanical analyses, geometric morphometrics and digital photogrammetry, enabled us to reconstruct some activities that an Upper Palaeolithic human group led inside a deep cave in northern Italy within a single exploration event about 14 ka calBP. A complex and diverse track records of humans and other animals shed light on individual- and group-level behaviour, social relationship and mode of exploration of the uneven terrain. Five individuals, composed of two adults, an adolescent and two children, entered the cave barefoot lightening the way with a bunch of wooden sticks (Pinus t. sylvestris/mugo bundles). While proceeding, humans were forced to move on all fours, and the traces they left represent the first report of crawling locomotion in the global human ichnological record. Anatomical details recognizable in the crawling traces show that no clothing was present between limbs and the trampled sediments. Our study demonstrates that very young children (the youngest about 3 years old) were active members of the human groups, even in apparently dangerous and social activities, shedding light on behavioural habits of Upper Palaeolithic populations.